High-temperature nanoindentation characterization of sintered nano-copper particles used in high power electronics packaging - Fan, Jiajie (2023)
Nano-copper sintering is one of new die-attachment and interconnection solutions to realize the wide bandgap semiconductor power electronics packaging with benefits on high temperature, low inductance, low thermal resistance and low cost. Aiming to assess the high-temperature reliability of sintered nano-copper die-attachment and interconnection, this study characterized the mechanical properties of sintered nano-copper particles using the high-temperature nanoindentation tests. The results showed that: firstly, the hardness and indentation modulus of the sintered nano-copper particles increased rapidly when the loading rate increased below 0.2 mN·s−1 and then stabilized, and decreased with increased applied load up to 30 mN. Next, by extracting the yield stress and strain hardening index, a plastic stress–strain constitutive model at room temperature for sintered nano-copper particles was obtained. Finally, the high temperature nanoindentation tests were performed at 140 ˚C–200 ˚C on the sintered nano-copper particles prepared under different assisted pressures, which showed that a high assisted pressure resulted in the reduced temperature sensitivity of hardness and indentation modulus. The creep tests indicated that high operation temperature resulted in a high steady-state creep rate, which negatively impacted the creep resistance of sintered nano-copper particles, while the higher assisted pressure could improve the creep resistance.